Діяльність Степана Бандери, ОУН-УПА за оцінкою російських істориків у 1991–2014 роках - Студьонова, Л. (Сiверянський лiтопис, 2015)
У статті розглядаються монографії, науково-популярні статті, інтерв’ю і лекції
російських істориків М. І. Семиряги, О. С. Гогуна, С. Г. Чуєва, А. Б. Зубова і К. М. Александрова, в яких ними дана оцінка діяльності С. А. Бандери, ОУН-УПА в роки Другої
світової війни і післявоєнний період в контексті нинішньої агресії Росії проти України. В статье рассматриваются монографии, научно-популярные статьи, интервью
и лекции российских историков М. И. Семиряги, А. С. Гогуна, С. Г.Чуева, А. Б. Зубова и
К. М. Александрова, в которых ими дана оценка деятельности С. А. Бандеры, ОУН-
УПА в годы Второй мировой войны и послевоенный период в контексте нынешней
агрессии России против Украины. Events of last in Ukraine, Russia’s annexation of the Crimea and military hostilities in
Donbas by russian army, supporting local separatists in such way, and also russion antiukrainian
advocacy a waked interest in one of the OUN leaders Stepan Bandera. The current
ukrainian government, the military and the common people ave called “banderas”, “ukrops”
and “ukrfascists”. That is due to the fact that Bandera is an important part of stalin ideological
myth, which is taken root not only in consciousness of elder generation but among the
youth too. That’s why one of the OUN leaders is still a terrorist, collaborate, authoritarian
leader and a symbol of fascist Ukrainian nationalism.
Modern Russia did not make either overcome or understanding the consequences of
bolshevism, which has brought a national disaster for nations of the former Soviet Union
including Ukrainian and russian.
Nowadays russian historian’s duty is to look objectively at Bandera’s life, to be honest and
not hypocritical in their own judgments even if it is unacceptable. There are such historians
in modern Russia who lives and works there. They say that well known facts of OUN (b)
leader’s life are not so important as commentaries to them.
Sharing this view, the author of this publication focuses on works of famous Russian
historians, who specialized in research of the problem of the collaborationism. This term
is used to in Second World War express a bitrayal of some people like an antipode for patriotism.
The are two synonyms of the bitrayal of Motherland in Soviet Union such as Red
Army General Andrei Vlasov and leader of the youth motion Orgnisation of Ukrainian
Nationalists Stepan Bandera.
For understanding what one of the liaders OUN and its military detachment UPA, author
made a review of modern historian’s works – antipods of official russian advocacy in press
and television. Monographs, non-fiction, lections and interview of young researchers are
considered in this review.
The eldest among them is M.I. Semyryaga – academician, professor, participant of Second
World War, colonel in reserve. After him is a Doctor of history A.B. Zubov. The generation of
guadragenerian is represented by S.G. Chuyev, O.S. Gogun, K.M. Alexandrov – candidates
of historical Sciences. Each of historians has its own approach to the disclosure of this topic,
but they are united in the conclusions:
- Bandera made his personality in culture centre of Europe but not in Ukraine, which
was as part of Russian Empire in early 20th century;
- Bandera is a highly educated fighter for independence of Ukraine and an enemy of
the Soviet Empire;
- Nation for Bandera is the highest value unlike the Bolsheviks, who considered the class
to be value;
- relation between banderas and Nazis were relations of tolerant Union;
- banderas were an independent force not the laborers;
- banderas fighted against totalitarianism of Hitler’s Reich and Stalin’s Empire;
– Their shed blood is a reaction on bolshevism, national passionarism;
- OUN’s violence was very similar to NKVD;
- in terms of history an armed struggle of OUN-UPA was national – liberation
anticommunistic motion.